Sparganosis due to Spirometra sp. (cestoda; Diphyllobothriidae) in captive meerkats (Suricata suricatta) - McHale, Brittany (Int J Parasitol Parasites Wildl, 2020)
We report three cases of sparganosis due to plerocercoids of the tapeworm Spirometra sp. in captive meerkats (Suricata suricatta) from a zoo exhibit in the southeastern United States. Two meerkats were euthanized, one due to an uncontrollable seizure and the other due to trauma, and at necropsy cysts containing cestode larvae were observed. A third meerkat had a subcutaneous nodule surgically removed, which contained similar larvae. The third animal died years later, and had numerous cestode larvae in the pleural and peritoneal cavities. The larvae were morphologically identified as plerocercoids of diphyllobothriidean cestodes. On necropsy, multiple nodules, ranging in size from 2.5 to 3.0 cm, were observed in the subcutaneous tissue and muscles. Multifocally, separating skeletal muscle fibers were longitudinal and transversal sections of cestode larva. Histologically, parasitic cysts contained large numbers of neutrophils and macrophages, admixed with proteinaceous material. Molecular and phylogenetic analyses confirmed that specimens from one of the meerkats belonged to the genus Spirometra and was closely related to Spirometra plerocercoids isolated from a snake from the United States and wild felids from South America. Meerkats likely became infected by ingesting infected second intermediate hosts, such as amphibians and reptiles that may have entered the exhibit. Management practices that minimize access of meerkats and other susceptible hosts to intermediate hosts should be implemented.